THE ROLE OF TIKTOK CELEBRITY AND DESTINATION AUTHENTICITY IN INCREASING TRAVEL INTENTION - Gozali, Tiffany; Tunjungsari, Hetty Karunia (International Journal of Application on Economics and Business, 2024)
Along with the development of the internet and social media, social media marketing is also increasingly being applied in various sectors, including the tourism sector. One of the social media that is currently widely used is TikTok. TikTok is a social media that displays short-duration content created by TikTok users so that various types of information are available according to the user's interests and needs. Social media such as TikTok plays an important role in increasing the travel intention because through TikTok celebrities or TikTok influencers, users can feel the authenticity of a tourist destination from a video so that it can influence the user's travel intentions. This research was conducted with the aim of determining the influence of TikTok celebrity involvement on travel intention with destination authenticity (object-based authenticity and existential authenticity) as a mediating variable. Data collection was carried out online using a questionnaire from Google Form and 203 answers from respondents could be used. Data analysis uses the PLS-SEM model and data is processed with SmartPLS 4.0. The results of this study show that celebrity involvement has no influence on travel intention, but has an influence when mediated by object-based authenticity and existential authenticity. Object-based authenticity has a positive effect on existential authenticity, object-based authenticity and existential authenticity have a positive effect on travel intention.